Contribution of voluntary monitoring in the training professionals: An experience report - Abreu, Manuela Crispim Morais; Magalhães, Marcela dos Santos (Research, Society and Development, 2024)
Academic monitoring is a teaching-learning mechanism to assist the production and understanding of university knowledge, performing pedagogical and scientific activities in education. Participation in monitoring programs in higher education, over the years, has become strongly present in graduation, where the importance of the program in the country towards teaching as a career choice is notable, providing the student with the opportunity to recognize themselves in area from the beginning in your chosen career. In this sense, the objective of this work is to demonstrate the contribution of the monitoring process in the pharmacy course through an experience report. This work is a descriptive study, experience report type, carried out at the Federal University of Amazonas, from March to July 2021 with the discipline of Cytology, Histology and Embryology remotely. The discipline monitors were responsible for monitoring theoretical classes, assisting teachers, providing guidance to students, correcting reports, answering questions and others. It was found that in addition to the difficulties already established in face-to-face teaching, the remote period brought new obstacles that made it necessary to strengthen the bond between students and monitors, as well as with teachers, providing more opportunities to resolve doubts and address the programmatic content in a way that facilitates the transmission of knowledge. In this way, it was observed that monitoring facilitated the teaching-learning process of pharmacy students in the discipline and the development of pedagogical skills with the connection between students and monitors.